A cross-sectional survey of material deprivation and suicide-related ideation among Vietnamese technical interns in Japan - Yamashita, Tadashi; Quy, Pham Nguyen; Yamada, Chika; Nogami, Emi; Seto-Suh, Erina; Iwamoto, Saori; Kato, Kenji (Frontiers in Psychology, 2024)
The economic struggles faced by many technical intern trainees in Japan include the necessity to remit money to their home country, debts owed to intermediaries facilitating their arrival, and reduced working hours due to the COVID-19 pandemic.Furthermore, there is concern that the pandemic may contribute to mental instability resulting from the significant life changes experienced by the trainees. This study examined the experience of material deprivation among Vietnamese intern trainees in Japan and explored the correlation between material deprivation and suicidal ideation.A cross-sectional study was conducted between September and October 2021, involving 310 Vietnamese technical intern trainees. Data from 200 participants were analyzed. The questionnaire included gender, age, duration of residence in Japan, proficiency in the Japanese language, income changes due to the COVID-19 pandemic, material deprivation status, and suicidal ideation. Suicidal ideation was assessed using the ninth item of the Patient Health Questionnaire-9. Logistic regression analysis was performed to investigate the relationship between material deprivation items and suicidal ideation.The mean age of the respondents was 26.0 ± 5.1 years, with 62.0% (n = 124) being male. Among the material deprivation items, 74.0% (n = 148) reported food 3 deprivation, 59.0% (n = 118) reported cellphone bill deprivation, and 55.0% (n = 110) reported medical expense deprivation. Suicidal ideation was reported by 23.0% (n = 46) of the respondents. The prevalence of suicidal ideation was associated with age (p = 0.031, odds ratio [OR] = 0.889, 95% confidence interval [CI] = 0.799-0.990), deprivation of food expenses (p = 0.003, OR = 3.897, 95% CI = 1.597-9.511), and deprivation of cellphone usage (p = 0.021, OR = 3.671, 95% CI = 1.217-11.075). Conclusions: Vietnamese technical intern trainees in Japan faced various forms of material deprivation, which correlated with a high prevalence of significant psychological issues. Suicidal ideation was influenced by factors such as age, deprivation of food expenses, and inability to pay cellphone bills. The experience of material deprivation could have intensified the mental health challenges faced by Vietnamese trainees, particularly in the demanding circumstances of the COVID-19 pandemic.